2013
DOI: 10.1155/2013/313081
|View full text |Cite
|
Sign up to set email alerts
|

Detection Limits of DLS and UV‐Vis Spectroscopy in Characterization of Polydisperse Nanoparticles Colloids

Abstract: Dynamic light scattering is a method that depends on the interaction of light with particles. This method can be used for measurements of narrow particle size distributions especially in the range of 2–500 nm. Sample polydispersity can distort the results, and we could not see the real populations of particles because big particles presented in the sample can screen smaller ones. Although the theory and mathematical basics of DLS technique are already well known, little has been done to determine its limits ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
228
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 412 publications
(259 citation statements)
references
References 46 publications
(57 reference statements)
9
228
0
3
Order By: Relevance
“…The observed absorption λ max at 405 nm was in line with the NPs size expected from the results of the relevant TEM and DLS analyses. 15,16 In addition, a great reproducibility intra-batches was observed confirming the method robustness (Table S1; Figures S1 and S2). The size and net particle charge of the as-synthesized AgNPs were determined through different techniques.…”
Section: Results and Discussion Synthesis And Characterization Of Agnpssupporting
confidence: 62%
“…The observed absorption λ max at 405 nm was in line with the NPs size expected from the results of the relevant TEM and DLS analyses. 15,16 In addition, a great reproducibility intra-batches was observed confirming the method robustness (Table S1; Figures S1 and S2). The size and net particle charge of the as-synthesized AgNPs were determined through different techniques.…”
Section: Results and Discussion Synthesis And Characterization Of Agnpssupporting
confidence: 62%
“…16,[18][19][20] Briefly, AgNP colloids sized 13, 33 and 46 nm were synthesized with silver nitrate and the mixture of sodium citrate and TA. In our previous study, we showed the crucial role of this mixture in the synthesis of monodisperse AgNPs compared to the synthesis carried out with sodium citrate or TA alone.…”
Section: Materials and Methods Synthesis Of Agnpsmentioning
confidence: 99%
“…However, it is well-known that for DLS measurements, there is a risk that small objects present in the sample can be screened by bigger ones and will not be seen during the measurement. 20 However, DLS results along with the STEM images allowed us to conclude that the tested colloids were monodisperse.…”
mentioning
confidence: 95%
“…Simplicity, sensitivity and selectivity to NPs and short measurement time are advantages of UV-Vis techniques. Therefore, the application of these techniques is increased in many fields of science and industry [133]. UV-Vis and infrared spectroscopies enable researchers to characterize nanoparticles, especially quantum dots, carbon nanotubes and fullerenes.…”
Section: Uv-vis Spectroscopymentioning
confidence: 99%